XTIP – the world's first beamline dedicated to the synchrotron X‐ray scanning tunneling microscopy technique. (14th April 2020) - Rose, Volker; Shirato, Nozomi; Bartlein, Michael; Deriy, Alex; Ajayi, Tolulope; Rosenmann, Daniel; Hla, Saw-Wai; Fisher, Mike; Reininger, Ruben
Abstract : A new beamline, XTIP, has been constructed at the Advanced Photon Source to deliver monochromatic soft X‐rays of between 400 and 1900 eV for the emerging synchrotron X‐ray scanning tunneling microscopy technique. Abstract : In recent years, there have been numerous efforts worldwide to develop the synchrotron X‐ray scanning tunneling microscopy (SX‐STM) technique. Here, the inauguration of XTIP, the world's first beamline fully dedicated to SX‐STM, is reported. The XTIP beamline is located at Sector 4 of the Advanced Photon Source at Argonne National Laboratory. It features an insertion device that can provide left‐ or right‐circular as well as horizontal‐ and vertical‐linear polarization. XTIP delivers monochromatic soft X‐rays of between 400 and 1900 eV focused into an environmental enclosure that houses the endstation instrument. This article discusses the beamline system design and its performance.